2004
DOI: 10.1002/cncr.20031
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic review of 58 patients with biliary papillomatosis

Abstract: BACKGROUND Biliary papillomatosis (BP) is a rare disease that is characterized by multiple numerous papillary adenomas in the biliary tree. The clinical features and outcome, however, are not well known. The authors retrospectively analyzed their clinicopathologic features and long‐term follow‐up results. METHODS Between March 1995 and January 2003, 58 patients were diagnosed with BP by cholangioscopic and histologic findings at a tertiary referral center, Asan Medical Center (University of Ulsan College of Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
179
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(186 citation statements)
references
References 27 publications
6
179
1
Order By: Relevance
“…From the view point of papillary proliferation, discrimination between IPN-B and biliary papillomatosis or cholangiocarcinoma of intraductal growth-type might be a problem. [29][30][31][32][33] We now speculate that most of biliary papillomatosis and cholangiocarcinoma of intraductal growth-type can be regarded as IPN-B, although a detailed clinicopathological study using a large numbers of cases is mandatory to conclude this issue. Biliary tumors with abundant mucin production have been called mucin-hypersecreting bile duct tumors.…”
Section: Discussionmentioning
confidence: 97%
“…From the view point of papillary proliferation, discrimination between IPN-B and biliary papillomatosis or cholangiocarcinoma of intraductal growth-type might be a problem. [29][30][31][32][33] We now speculate that most of biliary papillomatosis and cholangiocarcinoma of intraductal growth-type can be regarded as IPN-B, although a detailed clinicopathological study using a large numbers of cases is mandatory to conclude this issue. Biliary tumors with abundant mucin production have been called mucin-hypersecreting bile duct tumors.…”
Section: Discussionmentioning
confidence: 97%
“…2 These neoplasms can arise as either solitary or multifocal lesions within the biliary tree; in the latter scenario they are termed in classical parlance as 'biliary papillomatosis' . [3][4][5][6] Intraductal papillary neoplasms of the bile duct show considerable morphologic similarities to intraductal papillary mucinous neoplasms (IPMNs) of the pancreas. Both entities present with a prominent intraductal papillary component within larger-diameter ducts, both are mucinproducing, both harbour varying grades of dysplasia in the lining epithelium, and both exhibit distinct patterns of differentiation, such as intestinal and pancreatobiliary manifestations.…”
Section: Introductionmentioning
confidence: 99%
“…The accompanying jaundice arises as a result of the physical obstruction of bile outflow by the neoplasm itself or the viscous inspissated mucin. 5 There are no evident risk factors for IPNBs, although some studies have reported an association with longstanding biliary inflammation. 5,8 Because of the underlying risk for malignant transformation to invasive adenocarcinomas (cholangiocarcinomas) 5 and the obstructive nature of the lesions, resection with clear margins is the therapy of choice for IPNBs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, biliary papilloma is a rare neoplasm composed of papillary proliferation of biliary epithelium with delicate fibrovascular stalks, and multiple occurring biliary papillomas are known as biliary papillomatosis. 43,44 Billiary papilloma and biliary papillomatosis (BPs) are known to progress to invasive carcinoma. Some CCs also show mainly papillary proliferation in the bile duct lumen and also shows invasive lesions, and those cases are classified as the papillary type of bile duct carcinoma or intraductal growth-type of ICC (papillary CC).…”
Section: B Intraductal Papillary Neoplasm Of the Biliary Tract With mentioning
confidence: 99%